Cell encapsulated hydrogel microspheres as "building blocks" for producing 3D constructs - Praveen, S. (2014)
Cell encapsulation within hydrogel microspheres shows great promise in the field of tissue engineering and regenerative medicine (TERM). However, the assembling of microspheres as building blocks to produce complex tissues is a hard task because of their inability to place along length scales in space. We propose a proof-of-concept strategy to produce 3D constructs using cell encapsulated as building blocks by perfusion based LbL technique. This technique exploits the â bindingâ potential of multilayers apart from coating